Strategi Pengembangan Sumber Daya Aparatur Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kabupaten Simeulue - Hidayatun Mawaddah; Nodi Marefanda (UIR Press, 2022)
This article aims to find out the apparatus resource development strategy implemented by the Agency for Personnel and Human Resources Development in Simeulue Regency. The problem is focused on development strategies in the form of education and training (PIM), study permits and TPP grants. In this study, the theoretical reference is from Sondang P. Siagian which states that there are steps that must be taken to find out the benefits of developing human resources. The data were collected through interviews with the Secretary of BKPSDM Simeulue Regency, Head of HR Development, Head of Subsection and several apparatuses at BKPSDM Simeulue Regency and analyzed qualitatively. This study concludes that the implementation of the development strategy at the Simeulue Regency BKPSDM Office has been effective because it has been able to minimize the problems that existed previously.